Software Architecture Hour with Neal Ford. (O'Reilly Media, Inc., 2023)
Join us for a special conversation with Neal Ford and Chris Richardson, an experienced software architect, creator of the original CloudFoundry.com, and the author of POJOs in Action and Microservices Patterns. They'll discuss the concerns that you must consider when deciding between monolithic and microservice architectural styles, then they'll dive into how well each architectural style resolves these forces and how to evaluate the relative importance to your application of each of these forces. What you'll learn and how you can apply it Understand how to decide between monolithic and microservice architectural styles See what's coming next with software architecture This recording of a live event is for you because... You want the chance to hear from Neal Ford and Chris Richardson about microservices and software architecture and what the future might look like. You're looking for ways to grow your own skills and to act as an innovator in your organization. Recommended follow-up: Read Microservices Patterns (book) Listen to Microservices Patterns (audiobook) Read Monolith to Microservices (book) Read Building Microservices, second edition (book) Attend Microservices in 3 Weeks (live event) Watch Software Architecture Superstream: Microservices (live Superstream event recording).